1987
DOI: 10.1111/j.1365-2265.1987.tb01172.x
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Serum and Salivary Melatonin Concentrations and Urinary 6‐hydroxymelatonin Sulphate Excretion Rates: Two Non‐invasive Techniques for Monitoring Human Circadian Rhythmicity

Abstract: Although there is a circadian rhythm in blood melatonin concentrations in humans, the problems associated with frequent blood collection limit the use of this rhythm in the investigation of the circadian system and in the diagnosis and treatment of chronobiological disorders. Therefore, to establish a convenient, non-invasive technique for monitoring melatonin circadian rhythmicity, we compared the melatonin concentrations in blood samples collected from five subjects every 2-4 h over a 26 h period, with the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
2
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(99 citation statements)
references
References 17 publications
6
88
2
3
Order By: Relevance
“…Melatonin, an important circadian marker which synchronizes the internal hormonal environment according to the light-dark cycle, has been proved to be an effective antioxidant [31,44]. Melatonin is measurable in saliva and significant correlation was reported between melatonin concentrations in blood and saliva [35]. The study of Benot et al [5] reported the impact of melatonin on total antioxidant status (TAS) in human serum with maximal values of TAS at 1:00 a.m. which was similar to our study and contrasted the study of Borisenkov et al [6].…”
Section: Effect Of Circadian Rhythmmentioning
confidence: 99%
“…Melatonin, an important circadian marker which synchronizes the internal hormonal environment according to the light-dark cycle, has been proved to be an effective antioxidant [31,44]. Melatonin is measurable in saliva and significant correlation was reported between melatonin concentrations in blood and saliva [35]. The study of Benot et al [5] reported the impact of melatonin on total antioxidant status (TAS) in human serum with maximal values of TAS at 1:00 a.m. which was similar to our study and contrasted the study of Borisenkov et al [6].…”
Section: Effect Of Circadian Rhythmmentioning
confidence: 99%
“…Saliva and plasma melatonin levels are strongly correlated, with saliva levels ranging from 30 to 60% of plasma values (McIntyre et al 1987;Miles et al 1989;Nowak 1987;Vakkuri 1985).…”
Section: Melatonin Radioimmunoassaymentioning
confidence: 99%
“…1996). Although it was not until the 07.00 hours time that the EMA group had significantly less urinary melatonin metabolite than the control group, this most likely reflects a difference in plasma free melatonin levels 1-2 h earlier (Nowak et al 1987;Matthews et al 1991), the period during which the EMA insomniacs typically have difficulty maintaining sleep. Melatonin aIso acts as a chronobiotic (Lewy et al 1992;Dawson and Armstrong 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This assessment technique has been shown to be highly correlated with plasma free melatonin concentration and putatively with pineal melatonin secretion (Bojkowski et ul. 1987;Nowak et al 1987;Matthews et ul. 1991).…”
Section: Methodsmentioning
confidence: 99%